A mathematical modelling of economic restoration through agricultural revitalization in Nigeria - Ayoade, Abayomi Ayotunde; Farayola, Philip Iyiola (Penerbit Universiti Kebangsaan Malaysia, 2021)
Agricultural sector plays a major role in the economic growth of a nation. Apart from the provision of food which sustains human and animal life, the sector is the highest employer of labour in low income economies. The neglect of the sector due to the discovery of crude oil in Nigeria has led to the decline in the contribution of the sector over the years and an increase in the level of poverty. Based on that, a deterministic compartmental mathematical model was designed to study the least step needed to be taken by the government in the agricultural sector to revive the economy. Following the epidemic modelling approach, an analytic threshold that determined the effect of government effort on agriculture was derived. The model was studied qualitatively using the stability theory of nonlinear deferential equation and then quantitatively using hypothetical values for the model parameters to conduct the simulation. The qualitative result showed that the optimal agricultural output equilibrium of the model was locally asymptotically stable while the quantitative result showed that government effort to revive the agriculture was enough to restore the economy when the threshold quantity RI > 1. The implication of both the qualitative and quantitative results was that a drastic step had to be taken by the government to promote agriculture by allocating enough funds and land to the sector as well as encouraging farmers which would activate economic boom in the long run.